Student Perceptions of Language Advising as a Complement to the Flipped Classroom - Danica Anna D. Guban-Caisido (Studies in Self-Access Learning Journal)
The flipped classroom was implemented in an intermediate-level Italian class in the Philippines. Owing to the difficulties of the flipped classroom as described by existing literature, which includes a general lack of genuine motivation to access the materials needed for autonomous learning, language advising was conducted as a complementary tool to assist in the smooth implementation of the flipped classroom without the need to resort to extrinsic motivational strategies. Five students participated in the language advising sessions which were scheduled four times throughout the semester for each student with a duration of twenty minutes each. Through an open-ended questionnaire, the participants gauged their perceptions of the complementarity of the language advising sessions to the flipped classroom that was implemented throughout the semester. Using thematic content analysis for the open-ended responses, the following themes emerged from the students’ experiences: a sense of control of one’s own learning, personalized instruction, performance boosting and balance, and a fostering of student rapport.